Analisis Hasil Ukur Sensor Load Cell untuk Penimbang Berat Beras, Paket dan Buah berbasis Arduino - Unang Achlison; Bambang Suhartono (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Measurement results of load cell sensors sometimes has a significant difference even have the same weight, this is usually caused by several factors that affect the difference in the measured value, therefore on In this research, an analysis of the measurement results of a load will be carried out with the measuring object, namely rice, package and fruit. This analysis is carried out to determine the load which object is more efficient and accurate in do some weight calculation. The process of measuring weight using a load cell sensor is carried out based on Arduino device. After the measurement results are obtained then they are analyzed and compared between the measurement results of rice, package and fruit to determine the level of efficiency of the load cell sensor. Based on the experimental results of fruit, the measurement between the results to the real value is 4%. The measurement results of fruit have the efficiency of the load cell sensor